2020
DOI: 10.1038/s41598-020-62698-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant resistance does not compromise parasitoid-based biocontrol of a strawberry pest

Abstract: Plant nutritional quality can influence interactions between herbivores and their parasitoids. While most previous work has focused on a limited set of secondary plant metabolites, the tri-trophic effects of overall phenotypic resistance have been understudied. Furthermore, the joint effects of secondary and primary metabolites on parasitoids are almost unexplored. in this study, we compared the performance and survival of the parasitoid species Asecodes parviclava thompson on wild woodland strawberry (Fragari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Thus, herbivore preference for plants with lower levels of this compound could relate to a natural deterrence effect of this compound (Felton and Summers 1993), or innate avoidance as a behavioral adaptation against parasitism (as per the concept of "enemy free space" [Stamp 2001]). Pollinators on the other hand positively selected for dihydroxybenzoic acid: a phenolic that-in addition to serving as a direct defence, as discussed above-is also associated with indirect defence due to its strong association with parasitism success (Weber et al 2020a). Our finding of pollinator-mediated selection on a trait related to indirect defence corroborates prior results indicating potential pollinator selection on volatile signals involved in tritrophic interactions and the plant's "cry for help" (Kessler and Halitschke (2009).…”
Section: Selection On Indirect Defencesupporting
confidence: 86%
See 3 more Smart Citations
“…Thus, herbivore preference for plants with lower levels of this compound could relate to a natural deterrence effect of this compound (Felton and Summers 1993), or innate avoidance as a behavioral adaptation against parasitism (as per the concept of "enemy free space" [Stamp 2001]). Pollinators on the other hand positively selected for dihydroxybenzoic acid: a phenolic that-in addition to serving as a direct defence, as discussed above-is also associated with indirect defence due to its strong association with parasitism success (Weber et al 2020a). Our finding of pollinator-mediated selection on a trait related to indirect defence corroborates prior results indicating potential pollinator selection on volatile signals involved in tritrophic interactions and the plant's "cry for help" (Kessler and Halitschke (2009).…”
Section: Selection On Indirect Defencesupporting
confidence: 86%
“…Variation in direct and indirect defence was evidenced by the differential performance and preference of the herbivore and its specialist endoparasitoid (Asecodes parviclava Thompson [Hymenoptera: Eulophidae]) on diets of varying genotypic composition. Several primary and secondary compounds were ultimately identified as markers associated with either direct or indirect defence (Weber et al 2020a). We included the five compounds most strongly associated with defence: two carbohydrates (dehydroascorbic acid and myo-inositol) and three phenolics (catechin, dihydroxybenzoic acid, and shikimic acid).…”
Section: Trait Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…), it is a common pest of garden strawberry ( F×ananassa ) in Northern Europe ( Stenberg and Axelsson, 2008 ). We previously screened 86 woodland strawberry genotyped varieties for antibiosis and antixenosis against G. tenella ( Weber et al, 2020a ) and identified several primary and secondary metabolites that are associated with plant resistance ( Weber et al, 2020b ). Although the exact resistance mechanism requires further experiments, these results indicate the presence of a true intrinsic resistance.…”
Section: Methodsmentioning
confidence: 99%